3D Image Construction Using Single LRF Hokuyo URG-04LX - Hendriyawan, Achmad; Mohd Razali, Daud (2014)
Nowadays researchers who focus on robotic vision technology are facing with greater challenges, where the 2D technology has many flaws in robot navigation. Using 3D technology, the robot is able to make a more detailed map navigation making it easier to carry out its mission. 3D image is obtained by using the method of fusion between the Hokuyo URG-04LX with 6-DOF IMU consists of acceleration sensor and gyro sensor. IMU sensor outputs are the angle, speed, and position in 3D. However, only the value of the angle is used in this work. To eliminate noise in the sensors output, two types of filters are used; the gaussian filter used on the output 2D LRF, while the complementary filter is used on the output of the IMU sensor. The proposed systems has successfully generated a valid 3D image according to the indoor testing that has been done.